STRUCTURAL PERFORMANCE OF STORMWATER MODULE UNDER UNIAXIAL LOAD - Lee, Yeong Huei; Chai, Siew Liang; Abdul Rani, Mohd Hidayat; Ngu, Johnny Ong King (Journal of Civil Engineering, Science and Technology, 2022)
Geocellular plastic units or stormwater modules are popular to replace conventional drainage systems due to land limitations of urbanization. Most research focuses on stormwater management rather than its mechanical properties. Several cases were discovered where the failure was not due to material or manufacturing quality. As there is a lack on information of structural behaviour, this paper presents an experimental study of performance for stormwater modules under uniaxial load. There are four specimens for vertical load test and one for lateral load test. The vertical and lateral loads are applied separately to the specimens and the deflections are measured. From the obtained results, it is found that the module is able to resist 87.3486 kN and exhibits 12.3551 mm in vertical load direction. The column buckling is the failure mode of these specimens, and it is within the design limit of ASSTHO HS20 unfactored traffic load design. For lateral load, it can go up to 19 kN resistance, which is equivalent to a 3-meter depth design for the worst scenario with wet clay. The specimen is found to have failed in the excessive deflection which leads to the facture of the side cover. Further consultation is required in the detailed design using these stormwater modules underneath roads, buildings or car parks in order to obtain a more reliable stormwater management system.